Radiographic progression of large joint damage in patients with rheumatoid arthritis treated with biological disease-modifying anti-rheumatic drugs. Issue 4 (3rd July 2016) - Nakajima, Arata; Aoki, Yasuchika; Sonobe, Masato; Takahashi, Hiroshi; Saito, Masahiko; Terayama, Keiichiro; Nakagawa, Koichi
Abstract: Objectives : Radiographic progression of damage to the small joints in patients with rheumatoid arthritis (RA) is well known; however, it has not been studied fully in the large joints. In this study, we looked at the prevalence of radiographic progression of large joint damage in patients with RA treated with biological disease-modifying anti-rheumatic drugs (bDMARDs). Methods : A total of 273 large joints in the upper and lower extremities of 67 patients with RA treated with bDMARDs were investigated. Radiographs for tender and/or swollen large joints were taken at least twice during the study period (mean 18.6 months), and the progression of damage was evaluated. Results : Progressive damage was found in 20.9% of patients and 6.2% of joints. A multivariate analysis revealed that the Larsen grade (LG) alone was a risk factor for progressive damage. The LG cutoff value was determined to be 2.5 (sensitivity: 0.529, specificity: 0.805). Conclusions : The only factor to predict progressive damage was the LG of the joints with symptoms, and the damage must be stopped within LG II. Regular radiographic examinations for large joints should be performed in addition to routine examinations for small joints, such as the hand and foot.